Deepwater Fold‐and‐Thrust Belt Along New Caledonia's Western Margin: Relation to Post‐obduction Vertical Motions. Issue 10 (21st October 2017) - Collot, J.; Patriat, M.; Etienne, S.; Rouillard, P.; Soetaert, F.; Juan, C.; Marcaillou, B.; Palazzin, G.; Clerc, C.; Maurizot, P.; Pattier, F.; Tournadour, E.; et al.
Abstract: Classically, deepwater fold‐and‐thrust belts are classified in two main types, depending if they result from near‐ or far‐field stresses and the understanding of their driving and triggering mechanism is poorly known. We present a geophysical data set off the western margin of New Caledonia (SW Pacific) that reveals deformed structures of a deepwater fold‐and‐thrust belt that we interpret as a near‐field gravity‐driven system, which is not located at a rifted passive margin. The main factor triggering deformation is inferred to be oversteepening of the margin slope by postobduction isostatic rebound. Onshore erosion of abnormally dense obducted material, combined with sediment loading in the adjacent basin, has induced vertical motions that have caused oversteepening of the margin. Detailed morphobathymetric, seismic stratigraphic, and structural analysis reveals that the fold‐and‐thrust belt extends 200 km along the margin, and 50 km into the New Caledonia Trough. Deformation is rooted at depths greater than 5 km beneath the seafloor, affects an area of 3, 500 km 2, and involves a sediment volume of approximately 13, 000 km 3 . This deformed belt is organized into an imbricate fan system of faults, and one out‐of‐sequence thrust fault affects the seabed. The thrust faults are deeply rooted in the basin along a low‐angle floor thrust and connected to New Caledonia Island along a major detachment. This study not only provides a better knowledge of the New Caledonia margin but also provides new insight into the mechanisms that trigger deepwater fold‐and‐thrust belts. Key Points: New deepwater fold‐and‐thrust belt discovered off New Caledonia's western margin Origin of the deepwater fold‐and‐thrust belt is related to postobduction isostasic rebound Triggering of the deepwater fold‐and‐thrust belt is controlled by oversteepening of the margin